Self-harming: Reception in 27 steps of may film on Satu Persen community - Henny Sri Mulyani Rohayati; Putri Limilia; Nurvidha Qur’aini Suhaemi (ProTVF, 2023)
Background: The rise of self-harm content in 2021 in the motion picture can give different reactions to everyone who sees it. Not infrequently, the person’s reaction harms them, which in this research is the self-harming scene in 27 Steps of May film. The self-harm scene in the film is quite explicit by showing razor blades and flowing blood. Purpose: Find out how the dominant, negotiation, and opposition audience’s meaning regarding those scenes. Methods: This research used a qualitative method with a reception analysis approach using the encoding-decoding model from Stuart Hall. The subjects of this study were eight members of the Satu Persen Community on Telegram. Data collection techniques in this study used in-depth interviews and documentation techniques. Results: Intrinsic elements such as location, setting, and storyline in scriptwriting can also influence the audience’s meaning. The meaning of audience in research also varies. In the self-harm scene, one informant is dominant, and seven informants are in the negotiation position. There are three dominant informants and five negotiation informants in the self-harm scene location setting. For the flashback plot meaning of the self-harm scene, all informants are in a dominant position. There are no informants on the opposition’s position on the meaning of the self-harm scene, location setting, and the flashback plot meaning of the self-harm scene. The informants’ reading is influenced by personal experiences/others, sociocultural background, and duration of informants being members of the Satu Persen Community. Implications: Provide public awareness that different opinions in receiving messages are natural, and the public as active audiences can use films as learning media. However, be careful about the meaning that contrasts with their values.